Single-photon-level light storage in cold atoms using the Autler-Townes splitting protocol - Erhan Saglamyurek; Taras Hrushevskyi; Logan Cooke; Anindya Rastogi; Lindsay J. LeBlanc (Physical Review Research, 2019)
Broadband spin-photon interfaces for the long-lived storage of photonic quantum states are key elements for quantum information technologies. Yet, the reliable operation of such memories in the quantum regime is challenging due to photonic noise arising from technical and/or fundamental limitations in the storage-and-recall processes controlled by strong electromagnetic fields. Here, we experimentally implement a single-photon-level spin-wave memory in a laser-cooled rubidium gas, based on the recently proposed Autler-Townes splitting (ATS) protocol. We demonstrate the storage of 20-ns-long laser pulses, each containing an average of 0.1 photons, for 200 ns with an efficiency of 12.5% and a signal-to-noise ratio above 30. Notably, the robustness of ATS spin-wave memory against motional dephasing allows for an all-spatial filtering of the control-field noise, yielding an ultralow unconditional noise probability of 3.3×10^{−4}, without the complexity of spectral filtering. These results highlight that broadband ATS memory in ultracold atoms is a preeminent option for storing quantum light.